Contributions of the cryosphere to mountain communities in the Hindu Kush Himalaya: a review - Mukherji, Aditi; Sinisalo, Anna; Nüsser, Marcus (Regional environmental change, 2019)
There is a growing recognition of the contribution of the cryosphere to human societies. This is especially important in the Hindu Kush Himalaya (HKH), where poverty and vulnerability are high and climate change impacts on the cryosphere are strong. However, there is a lack of synthesized knowledge about the contributions of the cryosphere to high mountain communities. This paper uses a cryosphere service framework—a derivative of the ecosystem service concept—to classify different goods and services provided by the cryosphere. Case studies were selected using an adapted systematic review methodology. These studies were then synthesized and examined through the lens of critical political ecology. The review shows that while the cryosphere provides a whole range of goods and services for mountain communities, not all of these are well documented. Material services like the supply of water for irrigation and agriculture, and disservices such as disasters, are better documented than non-material services like the spirituality of landscapes. The majority of the case studies do not use an interdisciplinary lens. While some studies on irrigation discuss the physical basis and human organization of irrigation, the literature on disasters mostly focuses on the physical processes and at most generalized loss and damage assessments. Further, most case studies do not use the critical epistemologies needed to examine how politics, power, and intersectionality influence societal responses to changes in the cryosphere. The paper suggests that future studies adopt interdisciplinary collaboration to understand human impacts and adaptive responses through critical political ecology frameworks.